Skimmin Improves Insulin Resistance via Regulating the Metabolism of Glucose: In Vitro and In Vivo Models - Zhang, Guoqiang; Cai, Xin; He, Lingmin; Qin, Dingmei; Li, Hongwen; Fan, Xiaoming (Frontiers in Pharmacology, 2020)
Skimmin is the major pharmacologically active component present in Hydrangea paniculata, in the traditional Chinese medicine as an anti-inflammatory agent, and its anti-inflammation and anti-diabetic effect has had been studied in previous studies. The metabolism of glucose plays an important role in the pathophysiology of diabetes. Therefore, it was identified as an important target for improving diabetic. Hererin, we found that skimmin relieved the palmitic acid- and high fat and high sugar-induced insulin resistance. Furthermore, skimmin enhanced the glucose uptake via inhibiting reactive oxygen species (ROS) and reducing the level of inflammatory correlation factor. Meanwhile, skimmin reduced the glucose output by promoting PI3K/Akt signaling pathway and down-regulating the expression of glycogen synthase kinase-3β (GSK3β) and glucose-6-phosphatase (G6Pase). In Conclusion, skimmin can improve the insulin resistance by increasing glucose uptake and decreasing glucose output in vitro and in vivo.